PENGARUH LITERASI KEUANGAN DAN KEMUDAHAN BERTRANSAKSI TERHADAP MINAT PENGGUNAAN DOMPET DIGITAL (E-WALLET): STUDI KASUS KARYAWATI PT SMJ TEAM MEMBER SEWING LINE 1-40 GEDUNG UP 1 - Fanni, Maghfira Nur Tri; Dumadi, Dumadi; Roni, Roni (LP2M Universitas Bina Bangsa, 2025)
The financial services sector is one of the sectors that is very vulnerable to technological turmoil. This will change the business pattern of the financial services industry as a whole. Such as the emergence of technology-based financial companies or financial technology (fintech). The development of financial technology can change the way people conduct financial transactions and quickly turn cash transactions into non-cash. Revolutionary payment methods such as digital wallets will change the way we transact. To make transactions, e-wallets use digital tokens, which can be accessed through mobile devices, computers, or other internet devices. The purpose of the research was to analyze the influence of literacy on interest in using digital wallets/e-wallets; ease of transactions for interest in using digital wallets/e-wallets; financial literacy and ease of transactions together on the interest in using digital wallets/e-wallets in the employees of PT SMJ team member sewing line 1-40 building up 1. This type of research is quantitative research with the type of primary data obtained from questionnaire answers. The sampling technique was the Slovin formula with a margin error of 10% obtained by 96 respondents. The data were analyzed by descriptive statistical analysis test, classical assumption test, multiple regression analysis, and hypothesis test. The test is assisted by SPSS software. Financial literacy has a significant influence on interest in using digital wallets/e-wallets; ease of transactions has a significant influence on interest in using digital wallets/e-wallets; Financial literacy and ease of transactions together affect the interest in using digital wallets/e-wallets in PT SMJ team member sewing line 1-40 building up 1